Clinicopathological profile of non-hodgkin lymphomas affecting the parotid glands - Ribeiro De Araujo, Gabriela; Morais-Perdigão, Ana Luísa; Ambrósio Lima, Lucas; Cáceres, Cinthia Verónica Bardález Lopez de; Manuel Arteaga Legarrea, Juan; Rodrigues Gomes, Nathalia; Agustin Vargas, Pablo; María José Roman Tager , Elena; Antônio Rebelo Pontes, Hélder; Alves Mesquita, Ricardo; Ferreira de Sousa, Silvia; Paiva Fonseca, Felipe (Journal of Oral Diagnosis, 2024)
Objetivo: The aim of this study is to investigate the clinicopathological and immunohistochemical features of a series of lymphomas involving the parotid glands. Methods: All cases diagnosed in one pathology service from January 2008 and December 2018 were retrospectively retrieved, and the formalin-fixed paraffin-embedded tissue blocks were assessed for diagnostic confirmation. Clinical data were obtained from patients’ medical files. Results: We obtained twelve cases of NHL in the parotid glands representing nine MALT lymphomas, two follicular lymphomas (FL), and one diffuse large B-cell lymphoma, not otherwise specified (DLBCL, NOS). There was a predilection for the female sex (10F:2M), and in all cases it was possible to confirm the involvement of the parotid glands by macroscopic evaluation, imaging studies, or histologic assessment. Clinically, most of the lesions presented as asymptomatic swellings in the parotid region, although associated pain was reported in one case of FL, and three patients with MALT lymphoma had sicca symptoms. Conclusion: In conclusion, NHL affecting the parotid glands are usually of mature B cell lineage, usually representing low-grade subtypes, and frequently simulate other benign or malignant conditions.